Synthesis of zinc oxide nanoparticles and antibacterial activity against gram-positive and gram-negative bacteria - Muhamad Faez, Lukman (2017)
Zinc Oxide (ZnO) is a good anti bacteria that is used in many industry such as food industry and medicines. It is synthesized in many ways and in this experiment it will be carried out by microwave synthesis. Then the ZnO produced will be tested with Field emission scanning electron microscope (FESEM), UV-Vis spectrophotometry and Fourier transform infrared spectroscopy (FTIR). Its anti bacteria activity will be tested by disc diffusion method. The bacteria tested with the ZnO nanoparticles is the Gram positive and Gram negative bacteria. In UV-Vis the ZnO nanoparticles samples were measured to get absorption and normalized the spectra to compare peak shift. In FTIR a positive identification of every different kind of material is identified in the ZnO nanoparticles. While in FESEM the surface morphology and the size of the nanoparticles was examined. Zone of inhibition method was taken to evaluate the antibacterial activity of ZnO. Results from the UV-Vis is that the most optimum condition for the production of ZnO nanoparticle is at 1.0 M of NaOH, 500 Watt of irradiation power and 7 minutes of irradiation time. The FTIR shows that the ZnO nanoparticles exist based on the peaks that occurs at the wavelength 436 cm-1. Then at FESEM the particles of ZnO shows circular and have the same morphology and exist in the nano size which is in the range of 50nm to 70nm. Then growth curve was done to study the growth of E. coli and S. aureus and we got 8h as the optimum time to do the inhibition zone effect on the bacteria. Then we proceed with inhibition zone which shows a greater inhibition towards S. aureus compared to E. coli. It is concluded that ZnO nanoparticle does have antibacterial properties and to synthesize it is preferable under 1.0 M of NaOH, 500 Watt of irradiation power and 7 minutes of irradiation time.